LABA PER SAHAM DAN UKURAN PERUSAHAAN SEBAGAI PENETU PEMBAYARAN DIVDEN PADA PERUSAHAAN PERBANKAN YANG GO PUBLIC - Yuyut Dodi Indaya (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstraksiThis research was conducted with the aim of: 1) to know the effect ofEarnings Per Share on Dividend Payment, 2) To determine the effect of CompanySize on Dividend Payout.The population used in this study are all banking companies listed inIndonesia Stock Exchange (BEI) in the year 2012-2015. The sample selectionusing purposive sampling. Based on the criteria, acquired 11 companies sampledin this study. The method used in this study using multiple linear regression.Based on the analysis can be put forward some conclusions as follows: 1) Ftest results show that Earnings Per Share and Company Size have significanteffect on dividend payout. 2) The result of t test shows that Profit Per Share hassignificant effect to dividend payment while firm size has no significant effect todividend payment.Keywords : Earning Per Share, Firm Size, Dividend Payout